2005
DOI: 10.1902/jop.2005.76.4.508
|View full text |Cite
|
Sign up to set email alerts
|

New Rapid Polymerase Chain Reaction‐Immunochromatographic Assay for Porphyromonas gingivalis

Abstract: A diagnostic assay based on PCR-ICA was developed for the detection of P. gingivalis, and results were obtained visually in 3 hours. PCR-ICA will be a valuable tool for the rapid detection of target bacteria by chair side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…To our knowledge, this is the first time that this combination of PCR and immunochromatographic one-step detection is described for Listeria. The combination of both techniques into an assay for rapid detection of specific nucleic acid targets was already described for detection of the mecA gene from methicillin-resistant Staphylococcus aureus (MRSA) cultures [29], for direct diagnosis of Porphyromonas gingivalis [30], and for the identification of Mycobacterium tuberculosis [31].…”
Section: Development Of Nalfia For Listeria Detectionmentioning
confidence: 99%
“…To our knowledge, this is the first time that this combination of PCR and immunochromatographic one-step detection is described for Listeria. The combination of both techniques into an assay for rapid detection of specific nucleic acid targets was already described for detection of the mecA gene from methicillin-resistant Staphylococcus aureus (MRSA) cultures [29], for direct diagnosis of Porphyromonas gingivalis [30], and for the identification of Mycobacterium tuberculosis [31].…”
Section: Development Of Nalfia For Listeria Detectionmentioning
confidence: 99%
“…Analyte antigens in the sample bind to the antibodies and their presence or absence is then indicated by the extent of colour development at the test line as the labeled antibodies bind to it. During the last few years these lateral flow devices have been adapted for nucleic acid detection, [4][5][6] but because they are still based on haptens and antibodies they are unnecessarily complicated and expensive. In a typical example, nucleic acids are amplified with haptenylated primers and detected by sandwiching them between antibodies conjugated to GNPs and a nitrocellulose membrane striped with adsorbed antibodies (Fig.…”
mentioning
confidence: 99%
“…This method has been used for the rapid amplification and detection of pathogenic microorganisms in blood, sputum, and stool specimens from patients [Chow et al, 2008;Goldmeyer et al, 2008;Tang et al, 2010]. Takada et al [2005] reported a great potentiality of such technique using a similar sandwich immunoassay amplicon detection format for PCR assays on direct diagnosis of Porphyromonas gingivalis from periodontitis patients, and Soo et al [2006] developed PCR combined with immuno-chromatography test assay for detection of Mycobacterium tuberculosis.…”
Section: Resultsmentioning
confidence: 99%